(untitled) (Journal of the College of Basic Education, 2022)
In this research we discuss consolidating the role of Memory and Education of the Younger Generations , specially the educated masses of students and academics through the support of the concepts in the meeting , it is considered a pillar of sacrifice and love for the homeland where it is rooted in the memory of man also use it , to serve the community and not be just a memory emotions and pathos it does nothing to serve the community and the country